CTLA4‐Ig Directly Inhibits Osteoclastogenesis by Interfering With Intracellular Calcium Oscillations in Bone Marrow Macrophages. (16th July 2019) - Okada, Hiroyuki; Kajiya, Hiroshi; Omata, Yasunori; Matsumoto, Takumi; Sato, Yuiko; Kobayashi, Tami; Nakamura, Satoshi; Kaneko, Yosuke; Nakamura, Shinya; Koyama, Takuma; Sudo, Shunichi; Shin, Masashi; et al.
ABSTRACT: CTLA4‐Ig (cytotoxic T‐lymphocyte antigen 4‐immunoglobulin; Abatacept) is a biologic drug for rheumatoid arthritis. CTLA4 binds to the CD80/86 complex of antigen‐presenting cells and blocks the activation of T cells. Although previous reports showed that CTLA4‐Ig directly inhibited osteoclast differentiation, the whole inhibitory mechanism of CTLA4‐Ig for osteoclast differentiation is unclear. Bone marrow macrophages (BMMs) from WT mice were cultured with M‐CSF and RANKL with or without the recombinant mouse chimera CTLA4‐Ig. Intracellular calcium oscillations of BMMs with RANKL were detected by staining with calcium indicator fura‐2 immediately after administration of CTLA4‐Ig or after one day of treatment. Calcium oscillations were analyzed using Fc receptor gamma‐ (FcRγ‐) deficient BMMs. CTLA4‐Ig inhibited osteoclast differentiation and reduced the expression of the nuclear factor of activated T cells NFATc1 in BMMs in vitro. Calcium oscillations in BMMs were suppressed by CTLA4‐Ig both immediately after administration and after one day of treatment. CTLA4‐Ig did not affect osteoclastogenesis and did not cause remarkable changes in calcium oscillations in FcRγ‐deficient BMMs. Finally, to analyze the effect of CTLA4‐Ig in vivo, we used an LPS‐induced osteolysis model. CTLA4‐Ig suppressed LPS‐induced bone resorption in WT mice, not in FcRγ‐deficient mice. In conclusion, CTLA4‐Ig inhibits intracellular calcium oscillations depending on FcRγ and downregulates NFATc1 expression in BMMs. © 2019 American Society for Bone and Mineral Research.